2013
DOI: 10.1111/febs.12229
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia oklahomensis agglutinin is a canonical two‐domain OAA‐family lectin: structures, carbohydrate binding and anti‐HIV activity

Abstract: Burkholderia oklahomensis EO147 agglutinin (BOA) is a 29 kDa member of the OAA family of lectins. Members of the OAA family recognize high-mannose glycans and, by binding to the HIV envelope glycoprotein 120 (gp120), block the virus from binding to and entering the host cell, thereby inhibiting infection. OAA-family lectins comprise either one or two homologous domains, with a single domain possessing two glycan binding sites. We solved the structure of BOA in the ligand-free form as well as in complex with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…In the present study, we have determined the primary structure of KSA-2, and confirmed that it strongly resembles those of lower organisms, such as OAA from O. agardhii Sato and Hori, 2009), ESA-2 from E. serra , EDA-2 from E. denticulatum (Hung et al, 2015), MBHA from M. xanthus (Romeo et al, 1986;Koharudin et al, 2012), BOA from B. oklahomensis (Whitley et al, 2013) and PFL from P. fluorescens Pf0-1 (Sato et al, 2012) (Fig. 4), including its molecular size and the presence of tandemly repeated motifs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, we have determined the primary structure of KSA-2, and confirmed that it strongly resembles those of lower organisms, such as OAA from O. agardhii Sato and Hori, 2009), ESA-2 from E. serra , EDA-2 from E. denticulatum (Hung et al, 2015), MBHA from M. xanthus (Romeo et al, 1986;Koharudin et al, 2012), BOA from B. oklahomensis (Whitley et al, 2013) and PFL from P. fluorescens Pf0-1 (Sato et al, 2012) (Fig. 4), including its molecular size and the presence of tandemly repeated motifs.…”
Section: Discussionsupporting
confidence: 76%
“…This lectin family includes: OAA from Oscillatoria agardhii NIES-240 Sato and Hori, 2009;Koharudin et al, 2011), PFL from Pseudomonas fluorescens Pf0-1 (Sato et al, 2012), MBHA from Myxococcus xanthus (Koharudin et al, 2012), BOA from Burkholderia oklahomensis (Whitley et al, 2013), KAA-2 from Kappaphycus alvarezii (Sato et al, 2011a), BCA from Boodlea coacta (Sato et al, 2011b) and ESA-2 from Eucheuma serra (Sato et al, 2015). All of them share binding specificity for high-mannose N-glycans and have commonly two or four tandem repeats consisting of highly conserved sequences, which may lead to subtle difference in the degree of inhibiting activities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, antiviral activities of those lectins have been widely investigated specially in algal lectins: cyanovirin-N (CV-N) derived from cynobacterium Nostoc ellipsosporum, cynobacterium Oscillatoria agardhii agglutinin (OAA), Burkholderia oklahomensis agglutinin (BOA) and griffithsin (GRFT) from a red alga Griffithsia sp. (Balzarini, 2007;Franç ois and Balzarini, 2012;Huskens and Schols, 2012;Whitley et al, 2013). These lectins that specifically bind to highmannose glycan on viral envelope have been shown to inhibit infection of HIV (Boyd et al, 1997;Mori et al, 2005;Férir et al, 2014) as well as other enveloped viruses, including influenza virus , hepatitis C virus (Helle et al, 2006;Kachko et al, 2013), Ebola virus (Barrientos et al, 2003(Barrientos et al, , 2004, herpesvirus 6 (Dey et al, 2000), measles virus (Dey et al, 2000), coronaviruses (van der Meer et al, 2007;O'Keefe et al, 2010), and Japanese encephalitis virus (Ishag et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the X-ray data of sugar-free OAA suggests structural flexibility in binding site 2 (Figure S6), and inspection of additional X-ray structures that are available for several OAA homologues, with high conservation of binding site residues and sugar-protein interactions [67] , reveals that the sugar-bound conformation is frequently seen in sugar-free structures, reinforcing the notion that the bound conformation is more favorable in solution. This agrees with the observation that the motion between the ground and excited state detected by CPMG relaxation dispersion experiments, which occurs on a slower time scale than what is observed in the NOE data, does not coincide with that between free and bound conformations, extracted from chemical shift differences in the two 1 H- 15 N HSQC spectra.…”
mentioning
confidence: 78%
“…[15] In particular, the OAA carbohydrate recognition epitope on a high-mannose glycan was identified as 3α,6α–mannopentaose (the branched core unit of Man-9), which is a unique recognition element to OAA family lectins compared to all other anti-HIV lectins. [2,67] The X-ray crystal structures of both free and glycan-bound OAA revealed a β-barrel-like structure with two symmetrically positioned glycan binding sites at opposite ends of the barrel. [3] In the presence of sugar, the protein structure in binding site 2 shows a conformational change, namely the orientation of the peptide bond between W77 and G78 is flipped by ~180°.…”
mentioning
confidence: 99%